Mempelajari Ballad Bahasa Inggris Untuk Mendapatkan Kosa Kata Baru - Magdalena Baga (CV. Multi Kreasi Media, 2025)
By studying ballad poetry, students may get an understanding of the forms used in ballad poetry and even come across new terms. Ballad poetry is a type of English poetry, and this exercise will teach students new words while introducing them to it. High school students would benefit greatly from studying ballad poetry as a literary genre and an English language learning tool. Before learning English ballads, students are given an introduction to Indonesian ballad poetry. In order to better comprehend the tale told in the song, students are encouraged to expand their vocabulary. Students can practice their new vocabulary, particularly unfamiliar terms connected to the culture of the poetry's original setting, by reciting the words they acquired in this exercise.